Research on the Requirements of the Flavor Liquor Daqu for the Wheat Raw Material Quality - Chaosu LI; Yong REN; Hanwen TONG; Yubin LIU; Xiaoli WU; Ming LI; Miao LIU; Jianmin ZHENG; Ge WU; Chunbao GAO; Dong LING; Qing TANG; et al. (Shipin gongye ke-ji, 2023)
Wheat is the main component for producing the flavor liquor Daqu. It is essential to meet the raw material quality requirements for high-quality Daqu to breed special wheat varieties and simultaneously develop the supporting cultivation practices. From 2018 to 2020, a field experiment involving four representative wheat cultivars (Chuanmai 104, Mianmai 367, Xikemai 8, and Shumai 1671) and six nitrogen application rates (0, 45, 90, 135, 180, and 225 kg/hm2) in four different agro-ecological sites (Guanghan, Zitong, and Xichang in Sichuan Province, and Nanzhang in Hubei Province) in the upper and middle reaches of the Yangtze River basin was conducted. This study evaluated the main quality parameters of wheat raw materials and the quality of the flavor liquor Daqu. The results showed that, for most sensory and chemical parameters of Daqu, the main effects of year, location and variety, were all significant (P<0.05) or extremely significant (P<0.01). The total sensory score in 2019 was 9.7% higher than that in 2020. The mean total sensory score in Guanghan and Nanzhang location were 44.6 and 44.3 (maximum total score 60), respectively, significantly (P<0.05) different from that in Xichang location (39.7). The mean sensory score of Xikemai 8 and Chuanmai 104 were 45.4 and 43.8, respectively, which were significantly (P<0.05) higher than those of Mianmai 367 (42.2) and Shumai 1671 (42.0). The effects of nitrogen application rate on sensory score was not significant. Moreover, the values of the chemical parameters (acidity, saccharification power, liquefaction power, and ferment power) of Daqu for all treatments all met the requirements of "QB/T 4259-2011 flavor Daqu". Under different statistical methods, the raw material quality parameters associated with sensory evaluation of Daqu were different. Compared with other parameters, the comminution degree was more closely related to the sensory score of Daqu. For the samples with total sensory score≥45, the quantile values of 25%, 50% and 75% of comminution degree were 70.5%, 72.3% and 73.8%, respectively. In general, wheat raw materials with higher bulk density, falling value, water absorption of dough, medium to high grain opaque rate and suitable comminution degree are more suitable for Daqu production.